2012
DOI: 10.1371/journal.pone.0032238
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women Exhibit a Differential Bias for Processing Movement versus Objects

Abstract: Sex differences in many spatial and verbal tasks appear to reflect an inherent low-level processing bias for movement in males and objects in females. We explored this potential movement/object bias in men and women using a computer task that measured targeting performance and/or color recognition. The targeting task showed a ball moving vertically towards a horizontal line. Before reaching the line, the ball disappeared behind a masking screen, requiring the participant to imagine the movement vector and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Subjects with stroke were flagged for impairments on robotic parameters when their performance fell outside a parameter’s normative reference range, defined as the 95% confidence boundaries of control performance taking age [50-53], sex [54-56], and test-arm (dominant/non-dominant) [57-62] into consideration. Our primary analysis was concerned with the performance of the most affected arm in subjects with stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with stroke were flagged for impairments on robotic parameters when their performance fell outside a parameter’s normative reference range, defined as the 95% confidence boundaries of control performance taking age [50-53], sex [54-56], and test-arm (dominant/non-dominant) [57-62] into consideration. Our primary analysis was concerned with the performance of the most affected arm in subjects with stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Gender differences of female basketball players aged 12-13 years consists in the wider field of vision [36]. Our study shows, that male basketball players advantages of female basketball players are stipulated by their extensive basketball playing experience (4-5 years vs 1,5-2 years), which greatly affects the field of vision [39].…”
Section: Pedagogics Psychologymentioning
confidence: 67%
“…Studies concerning the adults showed higher rates of male process information ability to visual stimuli [8]. But during the objects recognition under the condition of barrier perception the response accuracy demonstrated by females was higher [39]. The visual input laterality, as a separate component of the psychological organization of a person [34], determines the peculiarities of the bioelectric activity transformation of the cerebral cortex under the influence of the sport activity [31].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
See 2 more Smart Citations